"Even if it didn't happen, it's true": The fantasy of geopolitics in the "post-truth" era. (May 2019) - Laketa, Sunčana
Abstract: In times when notions of political facts and objective truth are significantly challenged and undermined, this paper seeks to re-examine "old" questions of ideology by paying attention to economies of knowledge deemed fake and (officially) discredited. Using the "docu-fiction" film "Houston, We Have a Problem!" as a grounding point for examining the topological relationship between reason and fantasy inherent in geopolitics, I explore the contradictions within the film's production and reception, as it offers a powerful and complex account of illusion and reality that form our geopolitical worlds. The paper argues for geopolitics as a fantasy, where the fantasy is conceived as a material process, one placed firmly within the field of social practice and productive of social reality itself. The emotional grip of the fantasy is explored through humor, fun and laughter as forms of emotional purchase of geopolitics. To that end, this paper seeks to expand the field of popular geopolitics by offering a psychoanalytically-informed account of the emotional and affective economies involved in the production of geopolitical ideologies, and proceeds to explore how such fantasies of geopolitics continue to inform our contemporary social reality of "alternative facts" and "post-truth" politics. Highlights: Traditional attention to cinema in popular geopolitics is expanded. Fantasy is taken as a material condition of geopolitics. The ideological fantasy is productive of the social and geopolitical reality itself. "Post-truth" politics exemplifies the dynamics of fantasy in geopolitics.